Spatial and temporal recharge estimation of the basement complex in Nigeria, West Africa - Eniola Damilola Ashaolu (Journal of Hydrology: Regional Studies, 2020)
Study region: Osun Drainage Basin, Nigeria. Study focus: Estimating spatial and temporal patterns of recharge is important for sustainable groundwater resources management. This is especially true for data poor regions, such as the Basement Complex in Nigeria, which has shallow aquifers, a proliferation of wells and no efficient groundwater monitoring network. This study evaluates the performance of a spatially distributed monthly water balance model (WetSpass-M) in estimating groundwater recharge. The WetSpass-M model has moderate data demands, which allows for comprehensive assessment of recharge. New hydrological insights for the region: 27 % of the rainfall in Osun drainage basin becomes recharge, while the remaining is lost through evapotranspiration (43 %), surface runoff (21 %) and interception (9 %). September is the month with highest recharge, ranging between 0 and 73 mm in the north and 129 up to 213 mm in the south and northeast of the basin. The study revealed the significance of the applied water balance model in understanding the spatial and temporal status of recharge. Therefore, the spatial and temporal patterns of recharge should be taken into consideration in preparing a sustainable groundwater resources management plan for the Osun drainage basin. Artificial recharge might be adopted to store storm water runoff during wet periods to improve the groundwater supply in dry months. Also, monthly groundwater withdrawals should be regulated in relation to spatial and temporal recharge patterns. Keywords: Groundwater, Recharge, WetSpass-M, Groundwater management, Osun basin